Tribological Characteristics of Biolubricant Obtained by Transesterification of Grape Seed Oil - Thawan Fonseca Silva; Maria Marliete Fernandes de Melo Neta; Paulo Roberto Campos Flexa Ribeiro Filho; Francisco Murilo Tavares de Luna; Célio Loureiro Cavalcante (Lubricants)
Research on and the development of bio-based lubricants as alternatives to mineral-based lubricants have been encouraged worldwide owing to environmental concerns and the possible depletion of oil reserves. This study explored the use of grape seed oil (GSO), a byproduct of wine production, as a raw material for biolubricant synthesis. GSO contains a triglyceride molecule rich in unsaturated fatty acids, which is ideal for obtaining biolubricants. This study addresses the technical challenges of converting GSO into a lubricant by synthesizing methyl esters (FAME) via transesterification with 2-ethylhexanol to produce a biolubricant (BL) sample. The obtained products were characterized using Fourier-transform infrared spectroscopy and nuclear magnetic resonance spectroscopy to confirm the conversion of the molecules. The density, kinematic viscosity, and viscosity index were determined using the parameters established by ASTM. The tribological characteristics of BL were evaluated using a four-ball tribometer configuration. BL exhibited physicochemical characteristics comparable with those of an ISO VG 10 lubricant, a friction coefficient (FC) 40.82% lower than that of a hydrotreated mineral oil sample, and a smoother wear surface. These results indicate that the polarity of the ester functional group was efficient in producing a protective film on metal surfaces.